Survei Survei Event Quality pada Kejuaran Proliga Bolavoli di Pontianak Berdasarkan Persepsi Penonton - Firdaus, Rahmad; Andinata; Muhammad Suhairi, (Journal Sport Academy, 2024)
This study aims to examine and understand sports spectators' perceptions of service quality at the Proliga Volleyball event in Pontianak. The research uses a descriptive method with both qualitative and quantitative approaches. The survey method was employed, with data collected through questionnaires and analyzed using SPSS, utilizing percentage formulas from the survey data. The instrument used was a questionnaire. The study population included men and women who had attended the Proliga event, with a sample of 170 respondents located in Pontianak. The data analysis results showed that the estimated values for all variable relationships were greater than 0.5, with a value of 1.000. The indicators with average distribution ratings are: (1) game quality with sub-indicators: Skill Performance at 86.9% and Operating Time at 91.5%; (2) augmented service quality with sub-indicators: Information at 93.5%, Entertainment at 89.5%, and Concessions at 79.5%; (3) interaction quality with sub-indicators: Committee Interaction at 83.3% and Fan Interaction at 81.8%; (4) outcome quality with sub-indicators: Sociability at 83.4% and Valence at 92.7%; (5) physical environment quality with sub-indicators: Ambience at 92.7%, Design at 93.2%, and Signage at 88.5%. The analysis and discussion results indicate that the satisfaction of spectators' perceptions regarding the quality of the Proliga event was rated as good. The model test showed that all Event Quality criteria were met and satisfactory. Based on the analysis results, it is concluded that game quality, augmented service quality, interaction quality, outcome quality, and physical environment quality can be considered dimensions of service quality for the event.